The effect of pastoral assistance programs on mental health and resilience of congregational members who lost their jobs during the Covid-19 pandemic - Hutabarat, Bernard Maruli; Hutagalung, Stimpson; Hendriks, Alvyn Cesarianto; Ferinia, Rolyana (Universitas Islam Negeri Raden Intan Lampung, 2022)
This study aimed to determine the effect of the pastoral care program on the mental health and resilience of church members who lost their jobs during the COVID-19 pandemic. The research method used is quantitative using the Correlated T-test data analysis technique. The research found that the pastoral assistance program applied to congregations who lost their jobs during the COVID-19 pandemic had a significant positive effect on mental health. Likewise, the results of the analysis of the pastoral assistance program applied to congregations who lost their jobs during the COVID-19 pandemic on the resilience of church congregations. So it can be said that there is a significant effect of the pastoral assistance program on the mental health and resilience of the congregation who lost their jobs during the COVID-19 pandemic. Pastoral assistance programs are essential to provide, considering their various functions that impact mental health and provide a complete self-understanding for the community. The congregation is to be able to have resilient behavior where this is important to adapt and lead a normal lifestyle despite losing a job during the COVID-19 pandemic.